2019
DOI: 10.3390/socsci8040117
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Microfinance Institutions in Ethiopia: Integrating Financial and Social Metrics

Abstract: Since their inception in the 1970s, microfinance institutions (MFIs) have received increasing attention both from policymakers and academic circles. Using unbalanced panel data (2000–2017) from Ethiopia, in this paper, we investigated the performance of MFIs and its determinants on the one hand and whether or not mission drift exists on the other hand. To this end, we employed seemingly unrelated regression (SUR) and fixed/random effect panel models. The results indicate that, based on different outreach and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
(75 reference statements)
4
21
0
Order By: Relevance
“…On her study on a small sample of Indian MFIs, Kulkarni (2017) finds no indication of conflict between their outreach and efficiency objectives. On their study on Ethopian MFIs, Wassie et al (2019) find no evidence of conflict between social and financial performance of MFIs.…”
Section: Literature Reviewmentioning
confidence: 93%
“…On her study on a small sample of Indian MFIs, Kulkarni (2017) finds no indication of conflict between their outreach and efficiency objectives. On their study on Ethopian MFIs, Wassie et al (2019) find no evidence of conflict between social and financial performance of MFIs.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The profitability is associated with all MFIs operations and is influenced by many factors, including: Firstly, productivity: The result of Berguiga et al (2017) found that staff productivity was one of the determinants of return on assets and that the effect of staff productivity on return on assets was very significant for MFIs. According to Wassie et al (2019) the number of loan officers, loan officer productivity, and personnel productivity have a positive and significant impact on the financial performance of MFIs. In other words, productivity has a positive impact on the profitability of MFIs.…”
Section: Profitabilitymentioning
confidence: 99%
“…It is unlikely to attain sustained agricultural development without sustained utilization of improved agricultural technologies by farmers by providing rural financial services at all. 4 According to Wassie et al, 5 MFIs in Ethiopia attain their goal of serving the poor with higher and deeper outreach; showing positive impact. When we talk about impact, we are concerned not only with what changes have happen in selected indicators of welfare, but also with establishing how much such changes can be attributed to specific MF products or interventions.…”
Section: Background and Justification Of The Reviewmentioning
confidence: 99%